Planning of Marketing Strategy based on the Results of Analysis of Profitability Ratios and Activity Ratios (Case Study: PT Semen Indonesia Tbk) - Usada, Untung (UNIPA PRESS, 2024)
Semen Indonesia (Persero) Tbk is a manufacturing company engaged in cement production. This product is widely used for infrastructure development, so good cement quality is expected. Producers are expected to produce cement in accordance with consumer expectations and needs. The aim is to obtain high sales turnover. To meet sales targets, a good strategy is needed that is based on real conditions in the field. One of them is financial performance. Based on the financial performance report, especially the profit and activity ratios, it will be analyzed and used as a reference in determining sales strategies. The results of the financial performance analysis and SWOT analysis can formulate a sales strategy design.